Injectable and detachable heparin-based hydrogel micropatches for hepatic differentiation of hADSCs and their liver targeted delivery. (May 2018) - Hwang, Youngmin; Goh, MeeiChyn; Kim, Mihye; Tae, Giyoong
Abstract: A micropatterned heparin-based hydrogel system that can provide sustained release of multiple growth factors upon one time loading was prepared via photopolymerization and lithography and it was employed as a culture matrix for differentiating hADSCs into hepatic lineage. Mature differentiation of hADSCs into hepatic lineage in terms of gene expression and immunofluorostaining of hepatic markers, and functional characteristics such as glycogen storage ability and production of albumin and urea was observed on the soft hydrogel (∼400 Pa) when the gel elasticity was modulated. This optimal heparin-based hydrogel was used to prepare micropatches containing hepatic-differentiated cells by 1) micropatterning of the gel on a polyelectrolyte multilayer (PEM), 2) seeding of hADSCs and inducing hepatic differentiation, and 3) electrochemical retrieval of cell-attached micropatches. Upon i.v. injection, the retrieved cell micropatches showed a prolonged retention in the liver and promoted function compared to single cell injection in a rat model. In conclusion, this injectable and detachable miropatterned heparin-based hydrogel system could serve as a total platform for the stem cell differentiation under well-controlled microenvironment in vitro and for targeted delivery of the differentiated cells in vivo .